Automated External Defibrillator Geolocalization with a Mobile Application, Verbal Assistance or No Assistance: A Pilot Randomized Simulation (AED G-MAP). (4th May 2019) - Neves Briard, Joel; Grou-Boileau, Frédéric; El Bashtaly, Alaa; Spenard, Catherine; de Champlain, François; Homier, Valérie
Abstract: Objective: Shockable rythms are common among victims of witnessed public out-of-hospital cardiac arrest (OHCA), but bystander defibrillation with a public automated external defibrillator (PAED) is rare. Instructions from the emergency medical dispatcher and mobile applications were developed to expedite the localization of PAEDs, but their effectiveness has not been compared.Methods: Participants were enrolled in a three-armed randomized simulation where they witnessed a simulated OHCA on a university campus, were instructed to locate a PAED and provide defibrillation. Participants were stratified and randomized to: (1) no assistance in finding the PAED, (2) assistance from a geolocalization mobile application (AED-Quebec), or (3) verbal assistance. Data collectors tracked each participant's time elapsed and distance traveled to shock.Results: Of the 52 volunteers participating in the study (46% male, mean age 37), 17 were randomized to the no assistance group, 18 to the mobile application group and 17 to the verbal group. Median (IQR) time to shock was, respectively, 10:00 min (7:49–10:00), 9:44 (6:30–10:00), and 5:23 (4:11–9:08), with statistically significant differences between the verbal group and the other groups ( p  ≤ 0.01). The success rate for defibrillation in <10 minutes was 35%, 56% and 76%. Multivariate regression of all participants pooled showed that knowledge of campus geography was the strongest predictor of shock in <10 minutes (aOR =14.3, 95% CI 1.85–99.9). Among participants without prior geographical knowledge, verbal assistance provided a trend towards decreased time to shock, but the differences over no assistance (7:28 vs. 10:00, p  = 0.10) and over the mobile app (7:28 vs. 10:00, p  = 0.11) were not statistically significant.Conclusion: In a simulated environment, verbally providing OHCA bystanders with the nearest PAED's location appeared to be effective in reducing the time to defibrillation in comparison to no assistance and to an AED geolocalizing mobile app, but further research is required to confirm this hypothesis, ascertain the external validity of these results, and evaluate the real-life implications of these strategies.